Assessment on the Utilization of Completed Basic Education Research Fund in SOCSARGEN: Basis for Policy Enhancement - Libdan, Ildefonso; Robles, Ava Clare Marie; Rollo, Cornelio (JPAIR Multidisciplinary Research, 2023)
An assessment of the utilization of the Completed Basic Education Research Fund (BERF) in the divisions of South Cotabato, Sarangani, and General Santos City, Philippines, was conducted using a descriptive-correlational research design on the 40 BERF-recipient, teacher-researchers from School Year 2019-2021. It looked into whether the utilization had a significant influence on the proficiency of learners. The quantitative results revealed that completed BERF research was moderately utilized. Likewise, learners’ proficiency in the recipient school during the first quarter of School Year 2022-23 was very satisfactory. Furthermore, using a Spearman Rank correlation, the variables in utilizing completed BERF did not significantly influence learners’ proficiency in the recipient school. It can be seen that the research findings may not have reached the intended audience in a way that is accessible, understandable, and relevant to their needs. Accordingly, the learners had a very satisfactory performance. This can be attributed to their improved digital skills during the pandemic may have contributed to their face-to-face classes’ performance. The translation of research findings into actionable strategies and interventions was likely affected by other concerns in school management. Therefore, it is imperative to guarantee that the research supported by BERF closely corresponds with the unique requirements and difficulties students face in the school system.